(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
there are several important international treaties relevant to the protection of intellectual property rights. Of course, one of the most important treaties is the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), which all WTO members are required to sign. This agreement provides a set of agreed standards for the minimum protection of intellectual property rights around the world, . Along with TRIPS, there are many other international treaties that are relevant to intellectual property protection standards, such as the Paris Convention, the Berne Convention, and the WIPO Copyright Treaty.